Therapeutic outcomes of mandibular advancement devices as an initial treatment modality for obstructive sleep apnea. Issue 46 (November 2016) - Park, Pona; Jeon, Hyoung Won; Han, Doo Hee; Won, Tae-Bin; Kim, Dong-Young; Rhee, Chae-Seo; Kim, Hyun Jik
Abstract : Abstract: Although continuous positive airway pressure (CPAP) is a highly efficacious treatment for obstructive sleep apnea (OSA), there is a need for alternative treatment options, such as sleep surgeries and mandibular advancement devices (MADs), to overcome the limitations of CPAP. This study aimed to analyze the therapeutic outcomes of OSA subjects who were treated with a MAD, and to estimate the clinical impact of MAD as a first-line treatment for OSA. Forty-seven patients diagnosed with OSA received an adjustable MAD as an initial treatment. Drug-induced sleep endoscopic findings and sleep parameters (both pre-MAD and post-MAD treatment), such as apnea index, oxygen saturation, and degree of daytime sleepiness, were assessed retrospectively. The MAD treatment resulted in a significant reduction in apnea–hypopnea index, and also a significant elevation in lowest oxygen saturation. Satisfactory results of MAD treatment as a first treatment modality were observed in 27 patients, and a successful outcome was reached in approximately 72% of patients. The OSA patients who had lower body mass index and upper airway narrowing at the level of palate and tongue base showed relatively higher rates of a satisfactory outcome even in cases of moderate or severe OSA. These results suggest that the use of a MAD may be an alternative treatment option in OSA patients with retropalatal and retroglossal area narrowing regardless of disease severity. Additionally, MADs can be recommended as an initial treatment modality, and the effectiveness of MADs in achieving success may not be inferior to CPAP.